Manajemen Proses Pembelajaran Pembulatan Bilangan dengan Menggunakan Media Papan Anwar Sebagai Implementasi Kurikulum Merdeka Belajar - Laksmini, Margareta Diana; Baehaki, Imam; Ramdhani, Sendi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The Covid-19 pandemic has constrained face-to-face learning. Minister of Education and Research Nadiem Makarim designed an independent curriculum as an effort to overcome learning constraints. This is in accordance with Ki Hadjar Dewantara's concept of education which is based on freedom of learning. This study aims to analyze and describe teacher preparation, implementation, and evaluation of the management of the learning process of rounding numbers using anwar board media as an application of the independent learning curriculum for grade IV elementary school students. This research is a qualitative research. The type of research used is a case study approach to describe the research results and find a comprehensive picture of the application of the independent curriculum in learning to round numbers using the Anwar board media. The data validity test was carried out using the triangulation technique. The results of this study state that first, the implementation of learning to round numbers using Anwar board media as an application of the independent learning curriculum for grade IV students consists of the planning stage, initial assessment of learning, and implementation of learning, second, the evaluation of the management of the learning process of rounding numbers using Anwar board media as an application of the independent learning curriculum is aimed at knowing the learning progress of students and making adjustments to learning methods.